2019
DOI: 10.5194/acp-2019-1122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term historical trends in air pollutant emissions in Asia: Regional Emission inventory in ASia (REAS) version 3.1

Abstract: <p><strong>Abstract.</strong> A long-term historical emission inventory of air and climate pollutants in East, Southeast, and South Asia from 1950–2015 was developed as the Regional Emission inventory in ASia version 3.1 (REASv3.1). REASv3.1 provides details of emissions from major anthropogenic sources for each country and its sub-regions and also provides monthly gridded data with 0.25° × 0.25&am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…5). 45) The change in estimated EF BC in Kanto agrees well with the change in observed M BC in Tokyo. Although the EF BC from transport in Kanto (including diesel vehicles) decreased greatly during 2003-2015, the EF BC from industry slightly increased after 2011, which slowed the rate of decrease in total BC emissions after 2011.…”
Section: Emission Of Bc In Tokyo and Japansupporting
confidence: 77%
See 1 more Smart Citation
“…5). 45) The change in estimated EF BC in Kanto agrees well with the change in observed M BC in Tokyo. Although the EF BC from transport in Kanto (including diesel vehicles) decreased greatly during 2003-2015, the EF BC from industry slightly increased after 2011, which slowed the rate of decrease in total BC emissions after 2011.…”
Section: Emission Of Bc In Tokyo and Japansupporting
confidence: 77%
“…Temporal variations of total BC emissions (dots) and BC emissions from different sectors in (a) Japan and (b) Kanto during 2003-2015. Data from Kurokawa et al (2018) 45). …”
mentioning
confidence: 99%
“…The boundary concentrations were derived from the climatological means of the global chemical transport CHemical Atmospheric general circulation model for the Study of atmospheric Environment and Radiative forcing (CHASER;Sudo et al, 2002). The fixed anthropogenic emissions were taken from the monthly data of the Regional Emission inventory in ASia (REAS, version 2.1) with a 0.25 (Kurokawa et al, 2013) for 2008 (hereafter referred to as REAS2.1, 2008). We adopted the Global Fire Emissions Database (GFED; version 3.1) for the monthly emissions from biomass burning.…”
Section: Methodsmentioning
confidence: 99%
“…To better understand differences among anthropogenic emission estimates, we reviewed total emissions estimate differences for Asia, calculated for the same base year as this study. To do this, we compared the CREATE inventory outcomes with those produced by the REAS v3.1 (Regional Emissions Inventory in ASia v3.1) [44], MICS (the Model Inter-Comparison Study for Asia) [45], ECLIPSE v5a [46], and EDGAR v4.3.2 [47] inventories ( Figure 18). We found that the all-Asia CO, SO 2 , and NH 3 emissions estimates from CREATE showed a range similar to those of the other inventories, although NO x and VOC estimates averaged 26% and 21% lower, respectively, and the CREATE PM 2.5 estimates were 17% higher.…”
Section: Comparisons Between This Study and Other Emissions Datasetsmentioning
confidence: 99%
“…Comparing Chinese 2010 anthropogenic emission estimates using various emission inventories (unit: Tg/yr; * indicates that CO values have been divided by 10). (source: MICS [45], REAS [44], EDGAR [47], Wang et al [51], ECLIPSE [46], Y.Zhao et al [52], Y.Xia et al [53], B.Zhao et al [14], Globemiss [54], Y.Kang et al [49], R.Wu et al [55], P.Xu et al [50], Z.Lu et al [48])).…”
Section: Comparisons Between This Study and Other Emissions Datasetsmentioning
confidence: 99%